2023
DOI: 10.3390/tropicalmed8010060
|View full text |Cite
|
Sign up to set email alerts
|

Trichomonas tenax: A Neglected Protozoan Infection in the Oral Cavities of Humans and Dogs—A Scoping Review

Abstract: Trichomonas tenax is a flagellated protozoan parasite found in the oral cavities of humans and animals and has been associated with periodontal disease, the most prevalent inflammatory disease affecting them all. Studies have shown that T. tenax can cause damage to mammalian cells and secretes virulent proteins, such as cysteine. It is presently considered zoonotic. Despite the few studies that have been done, the pathogenicity of this oral protozoan is still not fully understood. A database search was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…The presence of T. tenax in periodontitis patients was higher than that in gingivitis patients, in accordance with results in other studies (Athari et al, 2007;Marty et al, 2017;Benabdelkader et al, 2019;Bracamonte-Wolf et al, 2019;Yaseen et al, 2021;Matthew et al, 2023). The explanation of the study's results could be supported by Ribeiro et al (2015) and Marty et al (2017), who revealed that the occurrence of T. tenax in the deep periodontal pocket may substantiate this role in periodontal dysbiosis.…”
Section: Discussionsupporting
confidence: 90%
“…The presence of T. tenax in periodontitis patients was higher than that in gingivitis patients, in accordance with results in other studies (Athari et al, 2007;Marty et al, 2017;Benabdelkader et al, 2019;Bracamonte-Wolf et al, 2019;Yaseen et al, 2021;Matthew et al, 2023). The explanation of the study's results could be supported by Ribeiro et al (2015) and Marty et al (2017), who revealed that the occurrence of T. tenax in the deep periodontal pocket may substantiate this role in periodontal dysbiosis.…”
Section: Discussionsupporting
confidence: 90%
“…The detection methods were unspecified in two studies and biochemical methods were used in one. We observed that many scientists have identified Trichomonas tenax through microscopic examination, with or without pre-staining, by visualizing pearshaped or elliptical cells with several flagella [91]. Microscopic examination was the primary detection method in forty studies, with thirty-nine using light microscopy and one employing phase-contrast microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the closely related sexually transmitted parasite Trichomonas vaginalis , which is human-specific, T. tenax was also commonly considered to be specifically associated with humans (Honigberg, 1990 ; Maritz et al, 2014 ). However, the use of sensitive molecular diagnostic tools has clearly demonstrated that T. tenax is common in the oral cavity of a broader range of hosts including, cats, dogs and horses and with some additional reports among birds (Kellerová and Tachezy, 2017 ; Matthew et al, 2023 ). There are also reports of the isolation of T. tenax from extra-oral locations including the respiratory tract, lymph nodes, salivary glands and the urogenital tract (Maritz et al, 2014 ; Brosh-Nissimov et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the ability of T. tenax to contribute, directly or indirectly, to the pathobiology of periodontitis, is still poorly understood. Indeed, there is a lack of data on the molecular and cellular basis of T. tenax interactions with host cells (Matthew et al, 2023 ), members of the microbiota, and its potential endosymbionts, three key factors considered important in modulating the pathobiology of T. vaginalis (Hirt et al, 2011 ; Mercer and Johnson, 2018 ; Riestra et al, 2022 ; Margarita et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation